Relationship between health-related quality of life and emergency department visit reduction in older adults - Kanninen, Jonna-Carita; Kautiainen, Hannu; Holm, Anu (Taylor & Francis, 2026)
The aim of this study is to assess the relationship between health-related quality of life (HRQoL) and the incidence of emergency department (ED) visits in a population of home-dwelling 75-year-olds. This study included home-dwelling older adults aged 75 in Western Finland, who participated in health screenings between 2020 and 2021, which included laboratory tests, self-reported questionnaires, and nurse interviews. HRQoL was measured using the 15D instrument, and participants were grouped into tertiles based on HRQoL scores. Demographic and clinical characteristics were analyzed, and ED visit incidence was evaluated per 1000 person-years (pyrs) over two years. Relationships between HRQoL dimensions and ED visits were presented as incidence changes and rate ratios with 95% confidence intervals (CIs). The study included 953 participants. Compared to those with lower HRQoL scores, participants with higher scores were more often male and married, made less frequent use of support services, had better mental health, were less frail, and functionally more independent. Improved nutritional status and hemoglobin levels, while fall risk, urogenital distress (UDI-6), and medication use decreased across tertiles. ED visit incidence decreased from over 300 per 1000 pyrs at low HRQoL (0.5) to about 50 per 1000 pyrs at high HRQoL (1.0). Improvements in specific HRQoL dimensions, especially sleeping and breathing, were significantly associated with fewer ED visits. Higher HRQoL has a relationship with fewer ED visits among home-dwelling older adults. Improvements in specific HRQoL dimensions, particularly sleeping and breathing, significantly reduce ED visit rates. These findings emphasize the importance of targeted HRQoL enhancements, comprehensive screenings, and preventive care to lower unplanned healthcare utilization.